2020
DOI: 10.3390/ijerph17217711
|View full text |Cite
|
Sign up to set email alerts
|

Meconium Exposure to Phthalates, Sex and Thyroid Hormones, Birth Size and Pregnancy Outcomes in 251 Mother–Infant Pairs from Shanghai

Abstract: Phthalates are hormonally active pollutants. In-utero exposure to phthalates has been reported to be associated with birth size parameters and pregnancy outcomes. However, previous reports were inconsistent. We examined the associations between meconium exposure to phthalates and the effects on birth size parameters, pregnancy outcomes and sex and thyroid hormones in 251 mother–infant pairs from a Shanghai hospital. We measured 10 metabolites of phthalates in meconium samples collected during the first 24h aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…Indeed, higher levels of the LMW phthalate metabolites (i.e., MMP, MEP, MiBP, MBP, and ΣLMW) were measured in of our study in participants recruited during the summer. Similar results were obtained for pregnant women, young children and general population in China(Guo et al, 2020;Yang et al, 2021). The reasons for the observed seasonal effects on metabolite concentrations remain unclear.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Indeed, higher levels of the LMW phthalate metabolites (i.e., MMP, MEP, MiBP, MBP, and ΣLMW) were measured in of our study in participants recruited during the summer. Similar results were obtained for pregnant women, young children and general population in China(Guo et al, 2020;Yang et al, 2021). The reasons for the observed seasonal effects on metabolite concentrations remain unclear.…”
supporting
confidence: 79%
“…Several studies in United States (Messerlian et al, 2016) and China (Mu et al, 2015; have reached the same conclusion. Additionally, maternal exposure to phthalates can increase the odds of preterm birth (Ferguson et al, 2019;Broe et al, 2019;Gao et al, 2019), and it is related to fetal birth size (Guo et al, 2020;Polańska et al, 2016;De et al, 2015). Moreover, maternal exposure to phthalates was observed to lead to gestational hypertension and gestational diabetes mellitus (Werner et al, 2015;James-Todd et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…An animal model study performed on rats (n = 24) showed significant positive associations for the progression of GDM through Di-n-butyl phthalate (p > 0.05 [45]). Consistent with this, 3 of 5 human studies observed positive associations between certain phthalates (monoiso-butylphthalate, mono-n-butylphthalate, mono-2ethyl-5-oxohexyl phthalate (p < 0.05) [46], monoethyl phthalate (95% CI:1.61 (1.10, 2.36) [47], mono-(2-ethylhexyl) phthalate (p = 0.019) [48]) and GDM. Two cohort studies by Shapiro e al.…”
Section: Pthalates and Gdm (N = 6)supporting
confidence: 58%
“…In this systematic review, the current evidence assessing environmental risk factors and GDM has been analyzed. Whilst we found clear evidence for an association between GDM and air pollution [29,[96][97][98][99][100][101][102][103][104][105][106][107], ambient temperature [31,[92][93][94][95], season [32,[85][86][87][88], cadmium [36,[80][81][82], arsenic [37,[70][71][72][73][74][75][76][77], POPs [55, 57-60, 62-64, 66, 67] and phthalates [45][46][47][48], the findings regarding phenols were rather heterogeneous. The results for adverse glycemic outcomes also showed clear associations regarding air pollution [98-100, 105, 107, 118-121], ambient temperature [92,94], season [32,85,…”
Section: Discussionmentioning
confidence: 80%
“…In addition, animal and epidemiological studies have reported that phthalate metabolites can penetrate the placenta and be retained in the fetus [ 14 , 30 , 31 , 32 ]. Biomarkers of phthalates in different specimens were used to assess the exposure of early life in the uterus, such as meocoin, serum, and amniotic fluid samples [ 14 , 21 , 33 ].…”
Section: Introductionmentioning
confidence: 99%